Analisis Yuridis Kewenangan Badan Permusyawarakatan Desa dalam Pembentukan Peraturan Desa - Yudha, Habriyanto; Subair, Laola; Salmi, Salmi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the authority of the Village Consultative Body (BPD) in the process of forming Village Regulations (Perdes) based on Law Number 6 of 2014 concerning Villages. The role of the BPD as an element of village governance and a partner of the village head is crucial, especially in drafting and establishing Perdes, which is an important instrument for the implementation of village autonomy. However, the implementation of this authority often hampers legal and factual challenges in the field, which impact the quality and effectiveness of village regulations. This study uses empirical legal research methods (socio-legal) to examine the conformity of normative rules with their implementation practices. Data were obtained through literature studies to collect secondary data (statutory regulations and legal literature) and direct interviews with BPD officials, the Village Secretary, and community leaders as primary data. Data analysis was conducted using descriptive qualitative methods. The results of the study indicate that normatively, the authority of the BPD in the formation of Perdes has been clearly regulated, including discussion and approval of draft Perdes. However, empirical research has found that factors such as a lack of legal understanding among BPD members, limited human resources, and inter-agency communication are key obstacles to the implementation of this authority. Therefore, it is concluded that efforts are needed to improve the institutional capacity of the BPD and synchronize regulations at the village level to ensure the effective and optimal formation of Village Regulations (Perdes) in accordance with the principles of village autonomy.